Relationship Between The Existence Of Larvae And The Incidence Of Dengue Fever In Gresik Regency In 2023 - Retna Gumilang; Bariah Ideham; Shinta Maulydiyah Basuki; Noer Farakhin (Sean Institute, 2024)
Background of the Study: The incidence of dengue fever has grown dramatically worldwide in recent decades. Most cases are asymptomatic or mild and self-managed, and therefore the true number of dengue cases is underreported . Objective: To analyze the relationship between the presence of larvae and the incidence of dengue fever in Gresik Regency. Stages of the research method: This type of research is an observational study with a cross-sectional approach. This research was conducted in Gresik Regency. Data collection was carried out in June - August 2023. The research unit was aggregate data in each Kelurahan Kab. Gresik with a sampling technique of the total population. Analysis to determine the relationship between the presence of larvae and the incidence of dengue fever was carried out using the Pearson correlation test.